The Influence of Democratic Leadership on Performance of Employees in The Population and Civil Records Office of Binjai City - Utami Leo, Yani; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
The purpose of this research is to determine and analyze the influence of democratic leadership on employee performance at the Binjai City Population and Civil Registry Office. This research was conducted using a causal associative quantitative approach. The sample used was 61 employees from the total number of employees. The research results show that democratic leadership has a positive and significant effect on employee performance. This is shown by the T-value of 8.389 > t table 1.67109 with a P-Value of 0.000 < 0.05. The regression coefficient shows that if democratic leadership is increased by 1 unit, employee performance will increase by 1,549 units assuming other variables remain constant. Apart from that, the results of the determination test show an Adjusted R Square value of 0.536 or 53.60%, which indicates that democratic leadership has a low influence on employee performance, while the remaining 46.40% is influenced by other factors that have not been studied. Thus, partially, democratic leadership has a positive and significant effect on the work of employees at the Binjai City Population and Civil Registry Office. This identifies that improvements in democratic leadership can contribute to improved employee performance.